Histopathological Analysis Of Liver Tissue For Post-Mortem Interval Estimation And The Impact Of Mechanical Trauma: A Forensic Study - Dr Pankaj Malia, Seema Kashyap , Dr NK Aggarwa (Cuestiones de Fisioterapia, 2024)
One of the most essential objectives of forensic pathology is the accurate estimation of the post-mortem interval(PMI), which is critical in criminal investigations. Establishing the time since death aids in reconstructing thesequence of events surrounding death, providing law enforcement with valuable insights that can help identifypotential suspects and evaluate alibis.1In cases where the time of death is not immediately evident, such asin unattended deaths, suspicious deaths, or deaths outside a hospital setting, the forensic pathologist mustrely on a variety of physiological changes that occur after death to estimate the PMI.